1992
DOI: 10.1002/em.2850190307
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis testing in Drosophila: VIII. Reexamination of equivocai results

Abstract: Twelve percent of the chemicals tested for mutagenicity by the National Toxicology Program (NTP) using the Drosophila sex-linked recessive lethal assay have been classified as producing equivocal results. We have reexamined the published data and the criteria used to determine mutagenicity in light of the historical distribution of the concurrent negative controls for this project. Many of the chemicals that originally produced equivocal results have been retested under code. As a result of changes to incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…It has been demonstrated that the sex-linked recessive lethal (SLRL) test is more sensitive than other Drosophila tests normally used for germ line genetic damage [Lee et al, 19831. This test has been utilized extensively by the National Toxicology Program for chemical mutagenesis testing [Foureman et al, 1994a,b;Mason et al, 1992;Valencia et al, 1985Valencia et al, , 1989Woodruff et al, 1985;Zimmering et al, 19891. The test has been standardized and results from individual chemical testing from different laboratories 0 1995 Wiley-Liss, Inc. are comparable.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the sex-linked recessive lethal (SLRL) test is more sensitive than other Drosophila tests normally used for germ line genetic damage [Lee et al, 19831. This test has been utilized extensively by the National Toxicology Program for chemical mutagenesis testing [Foureman et al, 1994a,b;Mason et al, 1992;Valencia et al, 1985Valencia et al, , 1989Woodruff et al, 1985;Zimmering et al, 19891. The test has been standardized and results from individual chemical testing from different laboratories 0 1995 Wiley-Liss, Inc. are comparable.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo, maltol-induced micronuclei in mouse bone marrow after intraperitoneal application (Hayashi et al, 1988). Negative results were obtained in a sex-linked recessive lethal mutation assay in Drosophila (Mason et al, 1992). However, the micronucleus assay is considered more relevant than the Drosophila assay.…”
Section: (Q)sar Predictionsmentioning
confidence: 99%
“…Injection 0.2 -0.3 μl, 10 000 ppm (10 000 μg/ml) Negative (Mason et al, 1992) Valid, however, test system considered of limited relevance. …”
Section: Drosophila Melanogastermentioning
confidence: 99%